Managing emerging fisheries of the North Kenya Banks in the context of environmental change. (1st August 2021) - Kamau, Joseph N.; Jacobs, Zoe L.; Jebri, Fatma; Kelly, Stephen; Kimani, Edward; Makori, Amina; Mwaluma, James; Mueni, Elizabeth; Ong'anda, Harrison; Palmer, Matthew R.; Popova, Ekaterina; Roberts, Michael J.; et al.
Abstract: The North Kenya Banks have long been considered an important emerging fishery with the potential to spur economic growth for local fishing communities. As a regionally important extension to the otherwise narrow East African continental shelf, the North Kenya Banks remain under studied with implications for efforts to develop a sustainable fisheries management strategy. The local marine ecosystem is known to be strongly influenced by wind driven upwelling processes with seasonal variability driven by the changing monsoon seasons being of particular importance. Nevertheless, the Western Indian Ocean is warming due to anthropogenic climate change with evidence indicating reduced ocean productivity in future. How the ecosystem of the North Kenya Banks will respond is currently uncertain but is of great importance due to the significance of coastal fishery resources to coastal communities, and growing Blue Economy initiatives to exploit the North Kenya Banks fisheries more widely. There is, however, limited knowledge of the processes influencing productivity over the North Kenya Banks regions and currently there is no management plan in place to sustainably manage the fishery resources. Here, information about the North Kenya Banks fisheries are examined in relation to environmental processes and threats from climate change impacts with suggestions for future research and management directions. Graphical abstract: Image 1 Highlights: The North Kenya Banks hosts important yet understudied emerging fisheries. These fisheries are susceptible to environmental variability. Climate change impacts on the fishery remain poorly studied. Understanding ecosystem responses critical to managing impacts on coastal communities.